Viabilidade e compatibilidade de pólen de diferentes genótipos de pereira no Rio Grande do Sul - Gonçalves, Ciane Xavier (2008)
Pear is a fruit tree that belongs to the family Rosaceae, subfamily Pomoideae and genus Pyrus. In Brazil, the pear production lays around 20 thousand ton, and this fact occurs mainly due to the lack of adapted cultivars to the climate conditions.The present work was developed with the objective to study the pollen viability and compatibility of different cultivars, selections and rootstocks for the pear culture. This work was divided into five batches: in the experiment 1 it was evaluated the in vitro germination of 14 genotypes of pear at different incubation times (2, 4 and 6 hours) in BOD incubator and in lightless condition at 25°C. In the experiment 2, the incubation time was set for each genotype according the best results obtained in the previous experiment and it was assessed different temperatures of incubation (20, 30 and 40 °C) on in vitro germination of 14 pear genotypes. The basic germination medium consisted of 100 g L-1 sucrose and 10 g L-1 agar. In the third experiment, time and temperature of in vitro incubation of the pollen grains were chosen conform to the previous experiments. It was evaluated the germination of ten pear genotypes under the influence of the increase of different combinations of boric acid and calcium nitrate to the basic germination medium. In the experiment 4 it was assessed the in vitro germination of pollen grains of pear genotypes (varying temperature and time of incubation) in BOD incubator, lightless and boric acid in three concentrations added to the basic germination medium. Experiment 5 evaluated the gametic compatibility in pear genotypes through pollen tube growth in pistil of flower 120 hours after pollination. Therefore, to the assessed genotypes it was evaluated the self-pollination either in the field or laboratory, cross-pollination or open-pollination. The germination percentage of the pear genotypes studied in the first experiment depends on time and sample. Among the pear genotypes assessed in the second experiment the temperature of incubation at 20°C is recommended and at 40°C is damaging for germination. In the third experiment, in general, either basic culture medium or enriched with 200 mg L-1 boric acid promote higher rates of in vitro germination of pollen grains of the pear genotypes; the germination percentage decreased whether enriched with 1200 mg L-1 of calcium nitrate, independently of boric acid concentration. For the pear genotypes evaluated in the fourth experiment it is recommended to germinate the pollen grains in either basic culture medium or enriched with 100 mg L-1 of boric acid. In the fifth experiment the ovule fecundation did not occur for most genotypes and pollination type; therefore, cross-pollination benefits fecundation.